Association between History of Gestational Diabetes and Exclusive Breastfeeding at Hospital Discharge. (August 2016) - Haile, Zelalem T.; Oza-Frank, Reena; Azulay Chertok, Ilana R.; Passen, Nina
Background: Exclusive breastfeeding is recommended in the first 6 months of life, especially for infants born to women with a history of gestational diabetes mellitus (GDM). Yet, women with a history of GDM face challenges with exclusive breastfeeding in the early postpartum period, a critical period for setting up longer term breastfeeding success. Minimal research has been published on associated risk factors for not exclusively breastfeeding. Objective: The purpose of this study was to examine the association between GDM and exclusive breastfeeding at hospital discharge. Methods: We conducted a cross-sectional analysis including 2038 women who participated in the population-based Infant Feeding Practices Study II between May 2005 and June 2007. Results: Gestational diabetes mellitus prevalence was 5.8%. The crude prevalence of exclusive breastfeeding at hospital discharge was 62.2% among women with GDM compared to 75.4% of women without GDM ( P < .01). After adjusting for sociodemographic, behavioral, and anthropometric factors, the odds of exclusive breastfeeding were lower among women with GDM compared to women without diabetes (odds ratio = 0.59; 95% confidence interval, 0.39-0.92). Furthermore, women who had gestational weight gain (GWG) below the Institute of Medicine guidelines had lower odds of exclusive breastfeeding compared to women who had normal GWG (odds ratio = 0.62; 95% confidence interval, 0.45-0.85). Conclusion: Women with GDM history and women with inadequate GWG may need additional education to promote exclusive breastfeeding during maternal hospital stay. It is important for health care providers to assess both factors when providing education on exclusive breastfeeding and to support these women's breastfeeding efforts in the early postpartum period to maximize potential for longer term breastfeeding success.